Implicações da concessão distinta de remunerações sobre o comprometimento organizacional na Advocacia-Geral da União - Zuccon, Roberto Carlos (2017)
The subject of this research is organizational commitment, with the objective of investigating the distinct award of remuneration to groups of administrative support staff in the Advocacia-Geral da União (AGU) and its implications on the understanding of distributive justice and on commitment in the dimensions: instrumental, normative and affective. The research was carried out with two groups: a) SPCE group (without a single structured career plan) formed by employees of the Institution's board, requisitioned / assigned in the AGU and b) and the CPCE group (with a structured career plan) formed only by requisitioned / assigned, in exercise in the AGU. The problem consists in the fact that these two groups receive differentiated remuneration, although in exercise in a same public organ. The theoretical foundation contemplated concepts of organizational commitment, understanding of organizational justice and reward system. The empirical study was performed at the AGU, following the model proposed by Mathieu and Zajac (1990), using two questionnaires. The first consists of social and functional questions about the three dimensions of organizational commitment using the Meyer and Allen scale (1997). The second focused on the perception of distributive justice. The data were treated using descriptive statistics; confirmatory factorial analysis; Cronbach Alpha consistency assessment, correlation analysis and multiple regressions. The main results reveal that: a) the higher the educational level the lower the affective, instrumental and normative commitment and the perception of distributive justice; b) correlations between the time of exercise in the institution were intense with distributive justice, significant with the affective commitment and with less expression with the dimensions of the instrumental and normative commitment; c) significant positive correlations between age with affective impairment and distributive justice; d) the CPCE sample, which receives higher remuneration than the SPCE group, presented a higher average in the perception of distributive justice and in the affective, instrumental and normative dimensions; e) the higher the educational level the lower the commitment and perception of the distributive justice of the individuals; f) positive correlation between remuneration and the affective and normative constructs in the SPCE sample and between that and the instrumental dimension in the CPCE group; g) significant correlation between distributive justice and three dimensions of impairment in the SPCE sample; h) confirmation of the independence between the affective and instrumental constructs; positive correlation between affective and normative impairment variables and between instrumental and normative variables; among others. The research was conducted within the line of Operations Management in the Public Sector, the technical product being a report in the format of executive summary, presenting the results to the managers of the AGU.